Augmented Landscapes and Delicate Machinery. (5th September 2013) - Smout, Mark; Allen, Laura
Abstract: Mark Smout and Laura Allen of Smout Allen describe how for them drawing is instrumental, enabling them to pursue preliminary investigations that establish 'a speculative method with which to examine the dynamic force of environmental and architectural processes'. This is illustrated by their Wet Lands: Architectural Waterscapes and Soft Infrastructures research project for London's Thames Estuary.